Relationship between highway location and quantitative terrain factors - Kunkitti, Asoke
The objective of the study was to determine whether or not certain relationship exist between quantitative terrain factors and the alignment established for Marikina-Infanta highway. One kilometer-grid cell was applied systematically throughout the area. Eight terrain factors were quantified in each of the test cells from data measured on topographic map. Quantitative map of each terrain factor was determined using computer prepared map. the relationship of eight terrain factors and MArikina-Infanta highway alignment was study by means of coincidence in optimization value in each cell.